PREVALENCE OF DIFFERENT SONOGRAPHIC STAGES AMONG NEWLY DIAGNOSED CASES OF CHRONIC HEPATITIS C: Sonographic Stages Among Chronic Hepatitis C - Ullah, Hidayat; Rehman, Atiq Ur; Zafar, Ayesha (Pakistan Armed Forces Medical Journal, 2017)
Objective: To find the prevalence of different sonographic stages among newly diagnosed cases of chronic hepatitis C. Study Design: Cross sectional study. Places and Duration of Study: Armed Forces Institute of Radiology and Imaging Rawalpindi, from June 2014 to December 2015. Material and Methods: All freshly diagnosed patients of chronic hepatitis C (CHC) with a positive anti-HCV and a positive PCR for HCV were subjected to ultrasound abdomen. The sonographic stage of CHC was decided as per previously defined criteria. Prevalence of each sonographic stage at the time of initial diagnosis was determined. Study population was divided in two groups of ’Early stage CHC’ (sonographic stage I, II) and ’Advanced stage CHC’ (sonographic stage III, IV, V). Student’s t-test was applied to compare the means of the values for different sonographic parameters in the two groups. Results: The study included 178 patients with male to female ratio of 1.86:1. Mean age was 47.5 ± 12.5 years. Prevalence of sonographic stages I, II, III, IV, Va and Vb in study population was 68% (n=121), 12% (n=21), 9% (n=16), 6% (n=11), 3% (n=5) and 2% (n=4) respectively. ’Early stage CHC’ and ’advanced stage CHC’ showed statistically significant (p-value <0.01) difference between average values of liver size, portal vein caliber, mean portal vein velocity and splenic size. Conclusion: The prevalence of advanced stage CLD (stage III-V) among newly diagnosed cases of chronic hepatitis C is as high as 20% despite the availability of diagnostic facilities.